Evaluation of the Clinical Learning Environment (CLE) Using the Postgraduate Hospital Educational Environment Measure (PHEEM) in Viewpoint of Dental Residents: A Multicenter Study in Iran - Zahra Salari; Azadeh Horri; Amin Tahmasbi; Raziyeh Shojayeepour; Fatemeh Jahanimoghadam (Kerman University of Medical Sciences, 2023)
Background: Continuous improvement of the quality of education requires continuous evaluation of the clinical learning environment (CLE) and identification of university students' perceptions and expectations. To this end, higher education must improve its quality and increase student satisfaction for its long-term success and survival.Objectives: The present study aimed to investigate and compare dental residents' attitudes toward the quality of the CLE.Methods: The participants in this cross-sectional descriptive study were all dental residents (n = 251) at three dental schools in Tehran, Mashhad, and Kerman who were studying in the academic year 2022-2023. The residents were selected using the census method. The Postgraduate Hospital Educational Environment Measure (PHEEM) was used to examine the quality of the learning environment in three areas: perception of autonomy (POA), perception of teaching (POT), and perception of social support (PSS). The collected data were analyzed using descriptive statistics independent samples t-test, correlation analysis, and linear regression analysis with SPSS software at a P value of less than 0.05 was considered statistically significant.Results: The mean scores for POA, PSS, and POT assessed by dental residents at Tehran, Mashhad, and Kerman universities were 108.54, 100.61, and 97.42 (out of 152), which were within the acceptable range. In addition, 44.88% of the dental residents had a good assessment of the CLE. Furthermore, all dental residents reported poor or negative attitudes toward POA. In addition, 34.76% of dental residents were positive about SSP and 50.70% of them had very positive attitudes toward POT.Conclusion: Although a majority of dental residents had positive views about the learning environment and its different educational and social aspects, they had negative assessments of the perception of autonomy (POA) as one of the essential factors in the learning environment. Thus, more attention should be paid to dental residents' perception of autonomy to promote the educational and social quality of dental schools.